The Effect of Biochar and Chicken Manure on Earthworm Population and Biomass in Corn Plantation(Zea mays L.) - Harja, Yandricho; Yusnaini, Sri; Prasetyo, Dedy; Lumbanraja, Jamalam (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2023)
Earthworms are organisms that can be an indicator of soil fertility. Chicken manure supplies nutrients to the soil for plants and the activity of organisms in the soil. Biochar can play a role in its relationship with soil ameliorants. Biochar together with other materials can improve diversity and improve soil mesofauna. The aim of the study was to study the effect of application of biochar, chicken manure on the population and biomass of earthworms, to study the correlation between organic C, soil pH, temperature, moisture content and corn production with earthworm population and biomass. The study was carried out from September 2020 to January 2021, using a randomized block design, treatments P0 (Urea + NPK), P1 (Urea + NPK + Biochar, P2 (Urea + NPK + Chicken manure), and P3 (Urea + NPK + Biochar + Manure chicken) with 4 replications Analysis with 5% level of variance The relationship between the supporting variables and the main variables was carried out by a correlation test. The application of chicken manure and biochar had no significant effect on the population and biomass of earthworms at 40, 60, and 90 DAP. positive correlation between population and biomass of earthworms with organic C and soil pH at observations 0, 40, 60 and 90 DAP. The results of the identification of earthworms, there is one genus Megascolex. There is a positive correlation between population and biomass of earthworms produced by wet weight and weight dry corn.